2020
DOI: 10.5194/isprs-archives-xlii-3-w12-2020-321-2020
|View full text |Cite
|
Sign up to set email alerts
|

Pasture Land Cover Change in São Paulo State, Brazil

Abstract: Abstract. Pastures are complex land covers with a variety of land use systems. This land cover occupies large areas in the globe and is mainly used for livestock production. Brazil is one of the largest livestock producers and has extensive pasture areas. We analyzed the pasture land cover change of the São Paulo State between the years 2000 to 2015. São Paulo was chosen as study case due to its large industrial and agricultural importance and its expressive land cover changes over past decades. It was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The relative and absolute change was calculated for each land cover type (see Supplementary Material, Table S3). Consistent with the literature [79,80], the most significant change within the 16-year study period of LULC was the rapid increase in sugarcane production, which corresponded to a net 128% increase in the percent of land used for sugarcane cultivation. The data evaluation showed that throughout more than half of the study period, from 2002 to 2014, pasture was the most represented land cover type in SP, although there was a steady yearly decline (net 43% decrease) over that period that coincided with the increase in sugarcane.…”
Section: Land Use Changessupporting
confidence: 82%
See 1 more Smart Citation
“…The relative and absolute change was calculated for each land cover type (see Supplementary Material, Table S3). Consistent with the literature [79,80], the most significant change within the 16-year study period of LULC was the rapid increase in sugarcane production, which corresponded to a net 128% increase in the percent of land used for sugarcane cultivation. The data evaluation showed that throughout more than half of the study period, from 2002 to 2014, pasture was the most represented land cover type in SP, although there was a steady yearly decline (net 43% decrease) over that period that coincided with the increase in sugarcane.…”
Section: Land Use Changessupporting
confidence: 82%
“…The practice of fluctuating between pasture and agricultural land use in Brazil is an established and documented technique, which is used by farmers to maintain the greatest gains from the land [45,85]. Newer and more sustainable techniques for cultivation, which result in less land degradation [86,87], and the increased profitability of agriculture compared to pasture lands [45,79,80,88] likely contributed to these land use changes. Additionally, of all the agricultural crops identified in the classification, sugarcane and soybeans are the most profitable [47].…”
Section: Discussionmentioning
confidence: 99%
“…Only 3% of São Paulo original Cerrado cover remains (Nalon et al 2020). Most of the remaining Cerrado and Atlantic Forest vegetation is immersed in a human-dominated matrix composed of pasture and agriculture (i.e., monocultures), and surrounded by the highest density of paved roads in Brazil (Durigan et al 2007, CNT 2018, Oliveira et al 2020). Furthermore, P. concolor is the top-predator most killed by vehicle collision in this region (Abra et al 2021).…”
Section: Study Areamentioning
confidence: 99%